New syllabus primary Mathematics workbook 2B - Yee, Dr Foong Pui; Pearlyn, Lim Li Gek; Hua, Wong Oon (Karachi ; Oxford university press, 2019)
New syllabus primary Mathematics (NSPM) is a comprehensive series which adopts a spiral design with carefully built-up mathematical concepts and processes. The Concrete-Pictorial-Abstract approach forms an integral part of the learning process through the materials developed for this series.
Keywords: Mathematics - text book; Oxford - Mathematics - text book; Problems - exercises